Innovative Work Behaviour in SMEs: The Positive Effect of Openness to Experience and Job Satisfaction - Fuhrer, Jorg (2016)
Innovation is a major concern of most organisations in today’s fast changing and highly competitive business environment. In particular, the individual innovative work behaviour of employees has recently attracted the notice of both scholars and practitioners. Small and mediumsized enterprises (SMEs) play a significant role in economies around the globe, and the innovative work behaviour of their employees is crucial to gain competitive advantage and leverage their performance against their larger rivals. However, understanding the underlying drivers of innovative work behaviour is a complex and multifaceted undertaking that all organisations have to manage. For almost 30 years, since the emergence of the Big-Five taxonomy, personality has been understood to affect organisational performance, thus creativity and innovation scholars moved their attention to personality characteristics. However, with the sound settlement and validation of these relationships, new models have to be examined to deepen the understanding of the individual drivers of innovative work behaviour. A sample of 124 employees from Swiss SMEs completed self-reported questionnaires to assess personality and job satisfaction regarding innovative work behaviour. The results indicated that job satisfaction moderates the relationship between openness to experience and innovative work behaviour, and moreover, also has a direct effect on the latter. Consistent with previous studies, openness to experience has been found to have a positive influence on innovative work behaviour, whereas conscientiousness, in contradiction with other research, has been found to have no direct effect on innovative work behaviour. In conclusion, the findings of this study demonstrate the importance of job satisfaction and openness to experience in promoting innovative work behaviour for organisations and scholars likewise.